2000
DOI: 10.1110/ps.9.1.145
|View full text |Cite
|
Sign up to set email alerts
|

Apoflavodoxin (un) folding followed at the residue level by NMR

Abstract: The denaturant-induced~un!folding of apoflavodoxin from Azotobacter vinelandii has been followed at the residue level by NMR spectroscopy. NH groups of 21 residues of the protein could be followed in a series of 1 H-15 N heteronuclear single-quantum coherence spectra recorded at increasing concentrations of guanidinium hydrochloride despite the formation of protein aggregate. These NH groups are distributed throughout the whole apoflavodoxin structure. The midpoints of unfolding determined by NMR coincide with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
42
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 36 publications
(44 citation statements)
references
References 33 publications
1
42
1
Order By: Relevance
“…For example, the GuHCl-dependent (un)folding of native apoflavodoxin gives rise to a steep change in tryptophan fluorescence emission in the corresponding transition region of (un)folding (midpoint of (un)folding Cm is 1.53 ± 0.01 M) [31]. In addition, NMR spectroscopic tracking of the unfolding of 21 residues distributed throughout native apoflavodoxin reveals coinciding midpoints of (un)folding (mean Cm of 1.48 ± 0.04 M GuHCl) [42], similar to the one obtained by tryptophan fluorescence. These experiments show a highly cooperative transition that happens due to unfolding of native apoflavodoxin, which leads to the denaturantdependent population of non-native protein.…”
Section: Accepted Manuscriptmentioning
confidence: 95%
“…For example, the GuHCl-dependent (un)folding of native apoflavodoxin gives rise to a steep change in tryptophan fluorescence emission in the corresponding transition region of (un)folding (midpoint of (un)folding Cm is 1.53 ± 0.01 M) [31]. In addition, NMR spectroscopic tracking of the unfolding of 21 residues distributed throughout native apoflavodoxin reveals coinciding midpoints of (un)folding (mean Cm of 1.48 ± 0.04 M GuHCl) [42], similar to the one obtained by tryptophan fluorescence. These experiments show a highly cooperative transition that happens due to unfolding of native apoflavodoxin, which leads to the denaturantdependent population of non-native protein.…”
Section: Accepted Manuscriptmentioning
confidence: 95%
“…There is, nevertheless, good evidence indicating that the FMN cofactor is not required: when the wild-type Anabaena protein is overexpressed and the cells are quickly harvested (in FMN limiting conditions), or when FMNbinding defective apoflavodoxin variants are expressed, large amounts of well-folded apoprotein are recovered (our unpublished observations and [19]). The stability of apoflavodoxin has been investigated using, in addition to the Anabaena [20][21] and Azotobacter [22][23] proteins, those of several Desulfovibrio strains and species [24][25][26]. It seems clear that the equilibrium thermal unfolding is three-state, so that a partly unfolded intermediate accumulates at moderately high temperatures (Fig.…”
Section: Folding Stability and Three-dimensional Structure Of Apoflamentioning
confidence: 99%
“…In the last 10 years, the flavodoxin folding mechanism has been outlined [15][16], the first three-dimensional structures of apoflavodoxin have been determined [34,38], the mechanism of apoflavodoxin/FMN recognition has been actively investigated [40][41][42][43][44], the stability of both the apo and holo forms are now largely characterized [20][21][22][23][24][25][26][27], the understanding of the role of the polypeptide in shaping redox potentials is much advanced [48][49][50][51][52][53][54][55][56][57][58][59][60][61][62][63] and new flavodoxin functions, beyond those of replacing ferredoxin, have been characterized. Indeed, flavodoxin is an essential protein for the survival of certain organisms, such as the pathogen Helicobacter pylori [39].…”
Section: Future Researchmentioning
confidence: 99%
“…Spectroscopic data show that the off-pathway folding species of flavodoxin is molten globule-like; its hydrodynamic radius is closer to the native state than to the unfolded state, its three tryptophans are solvent-exposed, and it has severely broadened NMR resonances due to exchange between different conformers on the micro-to millisecond time scale (18,29,30). An off-pathway intermediate is experimentally observed for all other ␣-␤ parallel proteins of which the kinetic folding has been investigated (i.e.…”
mentioning
confidence: 99%
“…We showed that at biologically relevant protein concentrations or by mimicking molecular crowding conditions present in cells, severe aggregation of the flavodoxin off-pathway species occurs (29,30). To further the understanding of the conformational properties of the flavodoxin molten globule, in this study, H/D exchange detected by NMR spectroscopy is used as a powerful technique that gives detailed information about a protein at the level of single amino acids.…”
mentioning
confidence: 99%